THE EFFECT OF ONLINE MARKETING (WEB BASED & ONLINE ADS) ON BRAND EQUITY NATIONAL SWITCHING COMPANIES THROUGH MGC (MARKETER GENERATED CONTENT) - Muhamad Fachreza; Yolanda Masnita; Kurniawati Kurniawati (Jurnal Ekonomi, 2023)
Online marketing is a way for a marketer to give related information about products/services provided by each company. In reality, this method is expected to be used as a connector for companies to create competitiveness for adding value into products/services. This study aims to see how Online Marketing can affect the Equity brand of a service product which is influenced by the type of media used, the content of the content, the type of content and also the combination of the type of media and the content of the content. In this study, the data taken will be processed using the SEM model. The results of the SEM analysis show that the type of media and content can affect the brand equity of online marketing and also the type of content. However, there are types of content that indirectly do not have a positive effect on brand equity from online marketing.